Tectonic deformation in El Salvador from combined InSAR and GNSS data - Portela, Juan; Staller, Alejandra; Béjar-Pizarro, Marta; Hamling, Ian J.; Hernández, Douglas (Tectonophysics, 2024)
The country of El Salvador, located at the convergent boundary of the Cocos and Caribbean plates, is subject to frequent seismic events and complex surface deformation. This paper presents the first Interferometric Synthetic Aperture Radar (InSAR)-based velocity field of El Salvador produced by combining InSAR and new GNSS data, which allows us to gain a deeper understanding of the intricate crustal deformation processes in the region. We use L-Band ALOS PALSAR images from five ascending and two descending tracks, as well as 171 continuous and episodic GNSS stations across El Salvador and the Caribbean. The inversion of GNSS and InSAR velocities along fault-perpendicular profiles enable us to assess the accommodation of tectonic deformation along the El Salvador Fault Zone (ESFZ), providing a better constraint on the behaviour of its main structures. Additionally, we are able to better understand how the deformation is transmitted at the western (Jalpatagua-Ipala) and eastern (Fonseca Gulf) terminations of the ESFZ. •We obtain the first continuous velocity field in El Salvador derived from InSAR data.•The El Salvador Fault Zone is coupled and the forearc is faster towards the west.•West of El Salvador, the deformation is distributed, coherently with a closing zipper.